Analysis of enzymes involved in starch phosphate metabolism - Samodien, Mugammad Ebrahim (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Genetics. Plant Biotechnology)) --University of Stellenbosch, 2009.